2009
DOI: 10.2463/mrms.8.65
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Slice Location to Assess Maximal Cross-sectional Area of Individual Rotator Cuff Muscles in Normal Adults and Athletes

Abstract: Purpose: We investigated appropriate slice locations for magnetic resonance (MR) imaging evaluation of the maximal cross-sectional area (CSA) of individual rotator cuŠ (RC) muscles in normal adults and athletes.Methods: We used a 1.5-tesla MR system with body-array and spine coils to obtain oblique sagittal T 1 -weighted shoulder images of 29 normal adults (16 men, 13 women); 6 national-level competitive swimmers (4 men, 2 women); 10 collegiate-level female badminton players; and 7 collegiate-level male rowers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Yanagisawa et al13 reported that the CSA of the supraspinatus muscle is maximal at the scapular notch and Thomazeau et al reported that the maximal CSA is found at the Y-view 10. However, because of the difficulty in measuring the supraspinatus thickness by US at the Y-view, we measured the supraspinatus thickness by US at the scapular notch and assessed its correlation with the CSA measured at the scapular notch and Y-view by MRI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Yanagisawa et al13 reported that the CSA of the supraspinatus muscle is maximal at the scapular notch and Thomazeau et al reported that the maximal CSA is found at the Y-view 10. However, because of the difficulty in measuring the supraspinatus thickness by US at the Y-view, we measured the supraspinatus thickness by US at the scapular notch and assessed its correlation with the CSA measured at the scapular notch and Y-view by MRI.…”
Section: Discussionmentioning
confidence: 98%
“…Yanagisawa et al13 used shoulder MRI to investigate the maximal CSA of the supraspinatus muscle and reported that the greatest CSA was measured at the scapular notch. Therefore, we considered the scapula notch to be a good site for measurement of the CSA for assessment of the supraspinatus muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, the anatomical cross‐sectional areas (ACSAs) of the RC muscles have been frequently evaluated in elderly subjects with tears in the RC tendons, especially the supraspinatus tendon (Zanetti et al, ; Shimizu et al, ; Gerber et al, ; Shen et al, ). In addition, the sizes and/or moment arms of RC muscles have been determined by MRI in healthy adult subjects (Juul‐Kristensen et al, ; Holzbaur et al, ; Vidt et al, ) or in various athletes with no history of shoulder injury (Yanagisawa et al, ). Moreover, Zanetti et al () demonstrated that the ACSAs of the supraspinatus and subscapularis progressively decrease in relation to increasing age in 70 asymptomatic subjects (35 men and 35 women, aged 21–70 years).…”
Section: Introductionmentioning
confidence: 99%
“…First, at the most lateral slice where the corpus scapulae and the spina scapulae had a Y-shaped appearance [ 18 ] and the spongiosa of the spina scapulae was observed (referred to as the “y-position”, Fig 2 ). Second, at a more medial slice, according to the method described by Yanagisawa et al[ 19 ] (referred to as the “set position”). The CSA of the supraspinatus muscle was measured 31 mm in males and 27 mm in females medial to the center of the glenoid cavity.…”
Section: Methodsmentioning
confidence: 99%